Peningkatan Kemampuan Berpikir Komputasional Siswa Berbantuan Scratch dengan Konsep Kebudayaan Indonesia dan Math-trail pada Pembelajaran Matematika - Maulana, Bagus Surya; Cahyono, Adi Nur (Program Studi Pendidikan Matematika Universitas Muhammadiyah Sukabumi (UMMI), 2024)
The background of this research is that the rapid pace of technology today creates new abilities, namely computational thinking ability to be improved. In addition, Indonesian culture also needs to be introduced to students today. This study aims to improve students' computational thinking ability using Scratch with the concept of Indonesian culture and Math-trail in mathematics learning. The subject of this research is class VIII students of Eka Sakti Junior High School, Banyumanik District, Semarang City with a total of 32 students with details of 14 girls 18 boys. Students' computational thinking ability is still low because there is no learning media that supports the improvement of students' computational thinking ability. This research uses quantitative methods. The suggestion from this research is the need to conduct further research that is more in depth to find out what factors make the increase.